Metaphor in Resistance Discourse: A Cognitive Linguistic Analysis of Sayyed Hassan Nasrallah’s Speeches - Ammar Kadhim Hadi, Assist. Lect. (lark, 2025)
Augmented by the Metaphor Identification Procedure (Pragglejaz Group, 2007), this research investigates the metaphorical framework of Sayyed Hassan Nasrallah’s political resistance discourse utilizing Conceptual Metaphor Theory (Lakoff & Johnson, 1980) and Critical Metaphor Analysis (Charteris-Black, 2011). Relying on a collection of seven speeches from 2013 to 2023, it finds prevalent conceptual metaphors and explores their cognitive, emotional, and ideological aspects. The analysis reveals a systematic usage of metaphor largely originating from the areas of Religion/Spirituality and War/Conflict supported by figurative frameworks from Natural Force, Structure/Fragility, and Health/Illness. These metaphors depict resistance as sacred, inevitable, and morally acceptable while developing collective identification and tactically delegitimizing adversarial forces. The article clarifies how metaphor functions as both a cognitive tool and a technique of persuasion by defining metaphors as structural or ontological and distinguishing between conventional and new expressions. The findings emphasize the basic need for metaphor in constructing ideological narratives, matching political opposition with cultural standards, and supporting legitimacy in conflict situations. This work adds to the disciplines of political linguistics, critical discourse analysis, and translation studies by demonstrating how metaphor generates socio-political reality rather than only reflecting it.